Might social attitudes be influencing nursing the dying? - Roberts, Emily (2014)
Abstract Aim To discuss the extent to which social attitudes affect nursing care of the dying. Background From experience as a student nurse I became interested in the effects of attitudes in society on the nurse and on the dying individual. I started to question the wider social context in trying to gain greater understanding to inform my nursing practice. I have observed great variations in behaviours and attitudes towards dying patients in different environments. I felt that an exploration of social attitudes affecting the nursing care of the dying would help towards a better understanding which may inform good nursing practice of the dying in the future. Method & Methodology The critical realist theoretical framework enables the critical review to be a process of exploration. Discussion The exploration of literature began by examining ideal types which showed how social attitudes towards death and dying changed and developed over time. Attitudes of the dying and those involved in nursing care were seen to be complex and in an evolving process, learned and adapted from past experience. Medicalization in contemporary society exerted key constraints upon the dying individual’s autonomy and nursing care. The nurse in contemporary society must be able to acknowledge the potential of medicine to shape social attitudes, create a ‘death denial’ attitude and constrain autonomy through poor communication practices. The micro, meso and macro social levels of analysis were considered in order to identify how social attitudes influence the quality of nursing care towards the dying across all social levels. It was found that several factors across the social levels affected nursing care. Conclusion Without an awareness of the effect which social attitudes can have upon nursing care, nursing care is not holistic and cannot fully help the individual towards optimising their precious last few years, months, days of life